2013
DOI: 10.4102/phcfm.v5i1.401
|View full text |Cite
|
Sign up to set email alerts
|

Breast examination as a cost-effective screening tool in a clinical practice setting in Ibadan, Nigeria

Abstract: How to cite this article:Ogunbode AM, Fatiregun AA, Ogunbode OO, Adebusoye LA. Breast examination as a cost-effective screening tool in a clinical practice setting in Ibadan, Nigeria. Afr J Prm Health Care Fam Med.Background: Breast cancer is a disease of public health importance. It results in high morbidity and mortality in women worldwide. The high morbidity and mortality from breast cancer can be decreased by measures targeted at early detection such as screening. Breast examination as a screening tool for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…BSE can be used as a reasonable and feasible approach in early detection and reduction of breast cancer mortality in developing countries. 24 Studies from India suggest, BSE can be used as a tool of creating breast health awareness among women and trained female health workers can play a promising role in disseminating this knowledge among women and increasing compliance to carry out BSE. 25,26,27 Utilisation of the services of our existing primary healthcare infrastructure and its facilities for opportunistic screening and health awareness classes by trained nonmedical community personnel such ASHA, anganwadi workers and Kudumbashree workers should be mentioned as one of the main activities in our future policies.…”
Section: Resultsmentioning
confidence: 99%
“…BSE can be used as a reasonable and feasible approach in early detection and reduction of breast cancer mortality in developing countries. 24 Studies from India suggest, BSE can be used as a tool of creating breast health awareness among women and trained female health workers can play a promising role in disseminating this knowledge among women and increasing compliance to carry out BSE. 25,26,27 Utilisation of the services of our existing primary healthcare infrastructure and its facilities for opportunistic screening and health awareness classes by trained nonmedical community personnel such ASHA, anganwadi workers and Kudumbashree workers should be mentioned as one of the main activities in our future policies.…”
Section: Resultsmentioning
confidence: 99%
“…It was only 12% on the study in Kiewit [ 7 ]. Similarly, a study conducted in Nigeria showed that breast self-examination was only 18.1% [ 8 ]. BSE was also 28.1% in a study conducted in Debre Berhan town, Ethiopia [ 9 ].…”
Section: Introductionmentioning
confidence: 99%